Incipient special interest tourism: Sea angling as recreational sport in South Africa - Christian M. ROGERSON; Jayne M. ROGERSON (GeoSport for Society)
Literature on special interest tourism has been expanding over the past 25 years. Although the growth of research interest and scholarship is relatively recent, the phenomenon of special interest tourism is not new and many of its forms enjoy a long history. Nevertheless, most existing international scholarship concentrates on contemporary issues. Against this background the aim is provide an alternative historical perspective on special interest tourism. Archival sources are used to analyse the evolution of sea angling as a recreational sport and incipient form of special interest tourism in South Africa. Arguably, sea fishing was a tourism asset and contributed to coastal resort development. In addition, as far back as the 1920s and 1930s tourism promotion in South Africa related to potential opportunities linked to special interests such as coastal recreational fishing.